THE CONTENT OF IMPLEMENTATION OF ACTIVITIES OUTSIDE THE CLASSROOM OR SCHOOL IN THE MEANINGFUL SPENDING OF FREE TIME IN STUDENTS - Ne’matova Laylo Laziz qizi (Web of Journals Publishing, 2024)
This article is about the technologies of the factors of implementation of activities outside the classroom or outside the school in the meaningful spending of free time in elementary school students, and the importance of activities outside the classroom and school is very important in raising them to be highly educated and deep-thinking and well-rounded individuals. there is a debate about it.
Keywords: Elementary class, primary time, extracurricular activities, technology, elementary school students, mature person, method, tool, actual problem.